2019
DOI: 10.1083/jcb.201812091
|View full text |Cite
|
Sign up to set email alerts
|

Engineered SUMO/protease system identifies Pdr6 as a bidirectional nuclear transport receptor

Abstract: Cleavage of affinity tags by specific proteases can be exploited for highly selective affinity chromatography. The SUMO/SENP1 system is the most efficient for such application but fails in eukaryotic expression because it cross-reacts with endogenous proteases. Using a novel selection system, we have evolved the SUMOEu/SENP1Eu pair to orthogonality with the yeast and animal enzymes. SUMOEu fusions therefore remain stable in eukaryotic cells. Likewise, overexpressing a SENP1Eu protease is nontoxic in yeast. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 72 publications
0
42
0
Order By: Relevance
“…Pdr6 has so far been a rather poorly studied shuttling NTR with just two import cargoes, subunits of TFIIA and a Wtm1 ribonucleotide reductase complex, being known. In the accompanying paper (Vera Rodriguez et al, 2019), we reevaluated its cargo spectrum and identified not only Ubc9 as a novel import cargo but also export cargoes, namely, the translation elongation factors eIF5A and eEF2, as well as the membrane trafficking components Pil1 and Lsp1. This defines Pdr6 as a bidirectional NTR or a biportin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pdr6 has so far been a rather poorly studied shuttling NTR with just two import cargoes, subunits of TFIIA and a Wtm1 ribonucleotide reductase complex, being known. In the accompanying paper (Vera Rodriguez et al, 2019), we reevaluated its cargo spectrum and identified not only Ubc9 as a novel import cargo but also export cargoes, namely, the translation elongation factors eIF5A and eEF2, as well as the membrane trafficking components Pil1 and Lsp1. This defines Pdr6 as a bidirectional NTR or a biportin.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant mouse Xpo4, human RanQ69L (5–180), human eIF5A, and S. cerevisiae eIF5A variants, as well as human Imp13, were expressed and purified as previously described (Aksu et al, 2016; Vera Rodriguez et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The coding sequence of full length human WNK1 was derived from a commercial expression vector (#RC218208, Origene, USA). Expression constructs needed to generate biotinylated anti-GFP nanobody for native purification from human cells are available from Addgene (#149336, #149334, #149333) (Pleiner et al, 2015;Pleiner et al, 2020;Vera Rodriguez et al, 2019). Expression constructs for the bdNEDP1, bdSENP1 and SENP EuB proteases were kind gifts of Dirk Görlich and are available from Addgene (#104129, #104962, #149333) (Frey and Görlich, 2014;Pleiner et al, 2018;Vera Rodriguez et al, 2019).…”
Section: Plasmids Antibodies and Sirnasmentioning
confidence: 99%
“…The expression of Biotin ligase BirA from pTP264 (Addgene #149334) was carried out as described before (Pleiner et al, 2020). The engineered SUMO Eu1 module is resistant to cleavage by endogenous eukaryotic deSUMOylases and thus allows stable isolation of nanobody-target complexes from eukaryotic cell lysates, followed by proteolytic release on ice in physiological buffer using the cognate SENP EuB protease (Vera Rodriguez et al, 2019). The expression of SENP EuB protease was carried out as described before (Pleiner et al, 2020;Vera Rodriguez et al, 2019).…”
Section: Expression and Purification Of Biotinylated Anti-gfp Nanobodymentioning
confidence: 99%
See 1 more Smart Citation